The Effect of Product Diversity and Price on Purchasing Decisions Mediated by Promotions: A Study on Shopee Application Users (Students of the Faculty of Economics and Business, University of Bandar Lampung) - Belinda, Sherliana; Barusman, Andala Rama Putra (Jurnal EMT KITA, 2025)
The aim of this study was to investigate the effects of product diversity and price on purchasing decisions, mediated by promotions, among Shopee application users. This study is quantitive research and utilizes primary data obtained directly from respondents through collecting questionnaire data via Google From. The population in this study consisted of students from the Faculty of Economics and Business, University of Bandar Lampung, totaling 936 individuals. Sampling was carried out using random sampling techniques and using the Slovin provisions, the sample obtained was 280 people. Data analysis was performed using PLS-SEM in the SmartPLS 4 application. The study's results show that product diversity, price, and promotion collectively have a significant impact on purchasing decisions, although product diversity itself does not affect purchasing decisions. Additionally, the study revealed that product diversity and price jointly influence promotion significantly, with the promotion variable mediating the impact of product diversity and price on purchasing decisions.